Statistical analysis of Co-efficient of friction during dry sliding wear behaviour of TiC reinforced Aluminium Metal Matrix Composites. (2018) - Baskaran, S.; Anandakrishnan, V.
Abstract: The present work involves the mathematical modeling and statistical analysis of coefficient of friction during dry sliding wear behavior of in-situ fabricated AA7075-TiC metal matrix composites under as-casted condition.Taguchi L27 orthogonal array experimental design is used to conduct the experiment and examine the significance of process parameters such as load, sliding velocity and sliding distance on coefficient of friction.The highly contributing significant parameterson coefficient of friction are identified by using Analysis of variance. Further a confirmation test was also conducted with the optimum parameter combination to validate the Taguchi results.